2014
DOI: 10.1634/theoncologist.2014-0182
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches in Anaplastic Thyroid Cancer Therapy

Abstract: Anaplastic thyroid cancer (ATC), accounting for less than 2% of all thyroid cancer, is responsible for the majority of death from all thyroid malignancies and has a median survival of 6 months. The resistance of ATC to conventional thyroid cancer therapies, including radioiodine and thyroid‐stimulating hormone suppression, contributes to the very poor prognosis of this malignancy. This review will cover several cellular signaling pathways and mechanisms, including RET/PTC, RAS, BRAF, Notch, p53, and histone de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 152 publications
0
35
0
1
Order By: Relevance
“…Despite the generally good prognosis, DTC patients with aggressive phenotypes, like extrathyroidal invasion or metastases, reveal a much higher disease recurrence rate, which is still challenging for clinical management (13,14). Recently, the Notch1 pathway has garnered great interest as a potential target of treating aggressive thyroid cancers (15-18). However, unlike the consistent observation on the loss of Notch1 expression in anaplastic thyroid carcinoma (17,19,20), the expression pattern and biological function of Notch1 in DTC are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the generally good prognosis, DTC patients with aggressive phenotypes, like extrathyroidal invasion or metastases, reveal a much higher disease recurrence rate, which is still challenging for clinical management (13,14). Recently, the Notch1 pathway has garnered great interest as a potential target of treating aggressive thyroid cancers (15-18). However, unlike the consistent observation on the loss of Notch1 expression in anaplastic thyroid carcinoma (17,19,20), the expression pattern and biological function of Notch1 in DTC are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, molecular biological studies have revealed that the mutation of the genes BRAF and N-RAS is associated with anaplastic transformation (17,18), and conventional cancer chemotherapy has been shifting to molecular-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is one of the most aggressive endocrine neoplasms, which has a high mortality rate despite the fact that ATC only accounts for 2% of all thyroid cancers (1). The median survival period of patients with ATC is less than half a year, and the 1-year survival rate is less than 20% after diagnosis (2)(3)(4). However, many patients spend money and ultimately succumb to ATC due to dismal prognosis, incurability, side effects, and complexity of treatment (5).…”
Section: Introductionmentioning
confidence: 99%